2015
DOI: 10.4028/www.scientific.net/amm.787.291
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation on Effect of Impact Velocity and Target Thickness in Magnesium Alloy AZ31B

Abstract: Recent research works indicate that magnesium alloy can be used for constructing light weight armor because of its density, which is 35% lower than aluminium and 77% lower than steel and also it exhibits superior vibration damping and better failure mechanisms than the contemporary ballistic materials. In this study, numerical simulations were carried out in a monolithic magnesium AZ31B plate using AUTODYN software to understand the effect of Impact velocity and plate thickness on the deformation of target pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Moreover, the numerical study is carried on models depicting the experimental procedure necessary to obtain a result on deformations and perforations [8,17]. From numerical investigations, they found there is a close correlation with the experimental results [5].…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…Moreover, the numerical study is carried on models depicting the experimental procedure necessary to obtain a result on deformations and perforations [8,17]. From numerical investigations, they found there is a close correlation with the experimental results [5].…”
Section: Introductionmentioning
confidence: 83%
“…As the Impact kinetic energy increases from 1569 J to 3888 J the residual kinetic energy decreases from 120 to 40 J. The numerical simulations using AUTODYN software were made on the target to correlate with the experimental results done by Tyrone et al [1] provides an out view of the ballistic penetration as it is shown in Figure 12 [5]. Fig.…”
Section: Studies Of Ballistic Test On Magnesium Alloysmentioning
confidence: 99%
See 3 more Smart Citations